Faktor-Faktor Yang Berhubungan Dengan Keluhan Nyeri Punggung Bawah (NPB) Pada Nelayan Di Negeri Laha - Rahmawati Indriyani; Ilyas Ibrahim; Zulfikar Lating (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Low back pain is discomfort felt in the lower back area, starting from the sacrum to the corner of the lowest ribs. Based on the results of an initial survey taken by interviewing 10 fishermen in Laha Country, 7 out of 10 fishermen felt or experienced pain in their lower back. The job of fishermen in Laha Country is to look for fish in the sea in a bent position and with minimal equipment, namely fishing nets. The type of research is analytical observational research with a cross sectional study approach. Population of fishing communities in Laha Country. The sampling technique used a probability sampling technique with simple random sampling of 91 respondents. The instrument uses a questionnaire. Data analysis used the chi square test with a significance level of p < 0.05. The research results showed that there was a relationship between age and NPB (P-value = 0.000), there was no relationship between body mass index and NPB (P-value = 0.379), there was no relationship between length of service and NPB (P-value = 0.134), There is a relationship between length of work and NPB (P-value = 0.001), and there is a relationship between work position and NPB (P-value = 0.003).